2018
DOI: 10.4046/trd.2018.0029
|View full text |Cite
|
Sign up to set email alerts
|

Revised (2018) COPD Clinical Practice Guideline of the Korean Academy of Tuberculosis and Respiratory Disease: A Summary

Abstract: Chronic obstructive pulmonary disease (COPD) results in high morbidity and mortality among patients nationally and globally. The Korean clinical practice guideline for COPD was revised in 2018. The guideline was drafted by the members of the Korean Academy of Tuberculosis and Respiratory Diseases as well as the participating members of the Health Insurance Review and Assessment Service, Korean Physicians' Association, and Korea Respiration Trouble Association. The revised guideline encompasses a wide range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 100 publications
0
32
0
Order By: Relevance
“…This was lower than adherence to the 2011 GOLD guidelines. This may be due to the fact that guidelines for the treatment of COPD in Korea still use post-bronchodilator FEV 1 as a basis for classifying patients into groups 10. In the Korean COPD guidelines, if FEV 1 is less than 60%, it is recommended that treatment correspond to GOLD group D. Therefore, the two guidelines could be mixed and used in real practice.…”
Section: Discussionmentioning
confidence: 99%
“…This was lower than adherence to the 2011 GOLD guidelines. This may be due to the fact that guidelines for the treatment of COPD in Korea still use post-bronchodilator FEV 1 as a basis for classifying patients into groups 10. In the Korean COPD guidelines, if FEV 1 is less than 60%, it is recommended that treatment correspond to GOLD group D. Therefore, the two guidelines could be mixed and used in real practice.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in GOLD group B are recommended to undergo treatment with a long-acting bronchodilator or consider a combination therapy with two bronchodilators depending on the initial symptoms and clinical progress. 13 Recently, it was reported that inhaled tiotropium could ameliorate the annual FEV 1 decline even in patients with COPD of GOLD stage 1 or 2. 14 However, our study had shown that in the actual field practice, the proportion of patients using inhalers fell short of that of patients treated with oral methylxanthines and LTRA, which take up far more than the recommended medicines in the selection of medication.…”
Section: Discussionmentioning
confidence: 99%
“…Lung function is an important trait of the respiratory system. Lung function measurements of the forced expiratory volume in one second (FEV 1 ) and the ratio of FEV 1 to forced vital capacity (FEV 1 /FVC) are used as criteria for chronic obstructive pulmonary disease (COPD) diagnosis and severity evaluation for pulmonary disease [1,2]. Although environmental factors such as smoking, air pollution and particulate matter influence lung function, the heritability of lung function has been reported to be around 40% [3,4].…”
Section: Introductionmentioning
confidence: 99%